2016
DOI: 10.1016/j.colsurfb.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity study in blood and tumor cells of laser produced medicines for application in fabrics

Abstract: Phenothiazine derivatives are non-antibiotics with antimicrobial, fungistatic and fungicidal effects. We exposed to a high energy UV laser beam phenothiazines solutions in water at 20mg/mL concentration to increase antibacterial activity of resulting mixtures. Compared to previous results obtained on bacteria, more research is needed about UV laser irradiated phenothiazines applications on cancer cell cultures to evidence possible anticancerous properties. Evaluation of the safety of the newly obtained photopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The pH difference is already discernible between pre- and post-hypergravity controls. This may be owing to the presence of transient photoproducts generated throughout the irradiation process (existing in solutions only 24–48 h after laser exposure [ 36 , 44 ]), absent at the time of measurements performed after the hypergravity campaign.…”
Section: Resultsmentioning
confidence: 99%
“…The pH difference is already discernible between pre- and post-hypergravity controls. This may be owing to the presence of transient photoproducts generated throughout the irradiation process (existing in solutions only 24–48 h after laser exposure [ 36 , 44 ]), absent at the time of measurements performed after the hypergravity campaign.…”
Section: Resultsmentioning
confidence: 99%
“…During the first 24 h-48 h following irradiation, new transient compounds are evidenced in UV-Vis absorption spectra like those responsible for the peaks at 454 nm and 486 nm generated in the first 15 min of laser exposure alongside the peaks at 637 nm and 882 nm in samples exposed to laser radiation ranging from 1 min to 120 min [95]. In Reference [96], a cytotoxicity investigation of newly generated molecules via laser exposure-as possible novel therapeutic agents-was described along with an in-depth analysis of the stability of phenothiazine solutions to identify the time frame within which laser-irradiated samples are stable and may be implemented in biomedical applications. The results highlighted dissimilarities in cell viabilities depending on the utilized endpoint assay and cell line type; however, the most significant differences in phenothiazine derivatives, such as CPZ, TZ, PMZ and promazine (PZ), were noticed to be related to the irradiation process.…”
Section: Terrestrial Microbial Concerns: Approaches For Multiple Drug Resistancementioning
confidence: 99%
“…For instance, the photoproducts mixture of irradiated CPZ and PZ solutions-considered to be the most efficient derivatives used on cell cultureswere not stable within the first 24 h following laser exposure; however, after that time interval, they became stable. The existence of transient compounds in solutions did not affect the results of the study, since it was carried out after the instability period [96]. Another report has shown that 15 min and 30 min laser exposed CPZ samples are highly efficient against methicillin-susceptible S. aureus (MSSA) ATCC 6538, MSSA ATCC 25,923, MRSA ATCC 43,300, Enterococcus faecium 17-VAR, E. faecalis ATCC 29,212 and Bacillus subtilis 6633 Gram-positive strains, in both the planktonic and biofilm-growing state as well [99].…”
Section: Terrestrial Microbial Concerns: Approaches For Multiple Drug Resistancementioning
confidence: 99%
“…Prior to the protocol, the cotton fabric underwent a cleaning procedure, consisting of 10 washing cycles in warm tap water, to eliminate contaminations. To verify the cleanliness of the fabric, the surface tension of the water used for washing was measured in each cycle with a Drop and Bubble Shape Tensiometer PAT-1 (SINTERFACE Technologies, Berlin, Germany), until the value of 71-72 mN/m was achieved, as shown in Simon et al and Morán et al [31,32]. Segments of 1 cm length were cut from a urinary catheter using a scalpel blade, then every piece was UV sterilized for 15 min on both sides.…”
Section: Immersion Of Medical Devicesmentioning
confidence: 99%